Female images in Chinese films: passivity, seduction, and resistance through the male gaze - Manyi Shi; Marlenny Deenerwan; Raja Farah Raja Hadayadanin (Cogent Arts & Humanities)
The representation of women has been an integral part of China’s century-long cinematic history. Using Laura Mulvey’s gaze theory as the theoretical framework, this study reexamines the role types of women in Chinese cinema from the gendered perspective of visual pleasure. Through textual analysis, this study explores the portrayal of female characters in Chinese films and categorizes them into three archetypes: passive-submissive, seductive-alluring, and epic-resistance types. The analysis focuses on iconic Chinese films such as Raise the Red Lantern (1991), Farewell My Concubine (1993), and Mulan (2009). By examining the identity and status of women within the visual pleasure provided by traditional narrative cinema, the study investigates how the male gaze shapes and influences female characters. Furthermore, the research reveals the marginalization and entrenched stereotypes of female roles in a male-dominated film industry while exploring broader possibilities for female representation.